Impact of Financial Liberalization and Governance on the Financial Development in Developing Countries - Ijaz, Anila; Idrees, Alvina Sabah (Archives of Business Research, 2016)
The study examines the impact of financial liberalization and governance on the financial development in developing countries. The study takes the sample of 48 developing countries and time period from 2000 to 2014. The study uses the domestic credit to private sector (percentage of GDP) as proxy of financial development and for measurement of financial liberalization Chin-Ito index is used. The study finds that financial liberalization alone does not have a significant effect on financial development however when financial liberalization is endogenized with governance then this impact becomes positive and significant. Good governance enhances the positive and significant impact of financial liberalization. Therefore, financial development of the developing countries can be enhanced by the financial liberalization followed by good governance.